2018
DOI: 10.1057/s41271-018-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution control and the occurrence of acute respiratory illness in school children of Quito, Ecuador

Abstract: Because of air quality management and control, traffic-related air pollution has declined in Quito, Ecuador. We evaluated the effect of a city-wide 5-year air pollution control program on the occurrence of acute respiratory illness (ARI). We compared two studies conducted at the same location in Quito: in 2000, 2 years before the policy to control vehicle emission was introduced, and in 2007. Each study involved ~ 730 children aged 6-12 years, observed for 15 weeks. We examined associations between carboxyhemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
0
13
0
2
Order By: Relevance
“…Because of air quality management and control, traffic-related air pollution has declined in Quito, a decrease that has been associated with a lower incidence of respiratory illness in schoolchildren. 32 Finally, the reduction in asthma symptoms could be related to the access and effectiveness of new medications and medical care, the latter mainly represented by an increase in physicians in the country from 10 808 in 2003 to 37 293 in 2017. 33 We also identified possible risk factors for current asthma, rhinitis and eczema.…”
Section: Discussionmentioning
confidence: 99%
“…Because of air quality management and control, traffic-related air pollution has declined in Quito, a decrease that has been associated with a lower incidence of respiratory illness in schoolchildren. 32 Finally, the reduction in asthma symptoms could be related to the access and effectiveness of new medications and medical care, the latter mainly represented by an increase in physicians in the country from 10 808 in 2003 to 37 293 in 2017. 33 We also identified possible risk factors for current asthma, rhinitis and eczema.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may be useful to identify potential intervention strategies, targeting the key molecules which enhance pulmonary NK cell function to protect against infections or to control an excessive activation of ILC2, thus decreasing the production of allergy-related cytokines and minimizing airway allergic inflammation. With respect to the development of preventive strategies, a comprehensive solution against harmful effects of air pollution on the respiratory health should require the implementation of and compliance with a broad range of policies to improve air quality [70].…”
Section: Discussionmentioning
confidence: 99%
“…This global reality is nothing different to Ecuador, a small developing Andean country in northwestern South America, as especially the high levels of air pollution occur in the country's biggest cities, due to their number of inhabitants, automotive fleet, and industries. Such conditions match those of one of the most polluted cities in the country, being the Metropolitan District of Quito (DMQ) (Estrella et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…These industries include a textile, plastics, automobile assembly plants, and metal melting clustering both at the northern and southern side of the city (Chiriboga, 2009;Distrito Metropolitano de Quito, 2014). However, Estrella et al (2019) argues that it has been a reduction of air contamination due to restrictions of car traffic circulation. Furthermore, a study by the country's census National Institute of Census and Statistics (INEC) indicated that in 2010 the motorized vehicles amounted to up to 1,226,349 automobiles, while in 2015 the figure reached a total of 1,925,368 automobiles, leading to some 57% of growth of its automotive park in only 5 years (INEC, 2019).…”
Section: Introductionmentioning
confidence: 99%